Evaluasi Implementasi Sistem Informasi Akuntansi Manajemen - Lastriana Sihotang; Aprieni; Farida Ratna Meilantika; Febrina Vidya Rachma S (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2024)
The Management Accounting Information System is an important tool in management and decision-making in an organization. With the advancement of information technology, many companies are switching from manual systems to computer-based systems to improve efficiency and accuracy in financial data processing. The implementation of the Management Accounting Information System not only aims to simplify the transaction recording process, but also to provide relevant and timely information for management in formulating business strategies and policies. However, despite the many benefits offered, the implementation of this system often faces various challenges. Some of these include a lack of user training, resistance to change, and integration with existing systems. Therefore, the evaluation of the Management Accounting Information System is very important to understand the extent to which the system can meet the needs of the organization